From Classroom to Catwalk: How Teaching Factory Management Cultivates Student Entrepreneurship and Career Readiness - Rukmosari Handayani; Widya Kusumaningsih; Ngurah Ayu Nyoman M (JURNAL AL-TANZIM, 2026)
This study aims to describe the implementation of Teaching Factory (TEFA) in increasing entrepreneurial interest and work readiness of students in the fashion design expertise program. This research is motivated by the gap between the competencies of Vocational High School graduates and the needs of the Business World and Industry, especially in the creative fashion industry sector. The novelty of this research lies in the study of TEFA implementation through a qualitative case study approach that integrates the theories of Experiential Learning, Constructivism, and Work-Based Learning in the simultaneous development of entrepreneurial competencies and student work readiness. This study uses a qualitative method with a case study design. The research subjects consisted of school principals, vocational teachers, students, and industry partners. Data were collected through in-depth interviews, participant observation, and documentation, then analyzed using the Miles and Huberman interactive model with data validation through triangulation. The results of the study indicate that TEFA implementation is carried out through an industry-standard production process, from planning and product manufacturing to marketing. This program contributes to improving students' technical skills, work ethic, self-confidence, work readiness, and entrepreneurial interest. Supporting factors include school support, teacher competence, industry partnerships, and learning facilities, while the main barriers are limited learning time and differences in industry work standards.